Brain‐Anatomy Differences in the Commission of Reversal Errors during Algebraic Word Problem Solving - Ventura‐Campos, Noelia; Ferrando Esteve, Lara; Miró‐Padilla, Anna; Ávila, César (Mind, brain and education, 2022)
An important line of research related to the resolution of word problems is the study of the cognitive processes involved when subjects translate problems into the language of algebra. One of the most common errors in problem‐solving is the reversal error (RE), which occurs when students reverse the relationship between two variables when translating equations from comparison word problems. The aim of this neuroeducational study is to investigate the brain anatomy differences between two groups, one group that commits RE and a second group that does not. Magnetic resonance images of 37 normal and healthy participants between the ages of 18–25 years were acquired. Differences in gray matter were assessed using voxel‐based morphometry analysis. Our results show that the RE group has a larger volume in the putamen, suggesting that these subjects have to make a greater effort to solve problems. LAY ABSTRACT We investigated the brain anatomy differences involved in problem‐solving with reversal errors. The results show that the group that commits reversal error compared to the group that does not, has a larger volume in the putamen, suggesting that these subjects have to make a greater effort to solve problems. These findings could help to better understand the relationship between brain development and the development of the human capacity for mathematical cognition mediated by educational experience.